2012
DOI: 10.1126/science.1225977
|View full text |Cite
|
Sign up to set email alerts
|

Insect Herbivores Drive Real-Time Ecological and Evolutionary Change in Plant Populations

Abstract: Insect herbivores are hypothesized to be major factors affecting the ecology and evolution of plants. We tested this prediction by suppressing insects in replicated field populations of a native plant, Oenothera biennis, which reduced seed predation, altered interspecific competitive dynamics, and resulted in rapid evolutionary divergence. Comparative genotyping and phenotyping of nearly 12,000 O. biennis individuals revealed that in plots protected from insects, resistance to herbivores declined through time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
449
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 420 publications
(475 citation statements)
references
References 35 publications
20
449
3
3
Order By: Relevance
“…Recent studies have shown that the heterogeneous distribution of herbivores can shape plant defensive chemistry above ground [7][8][9]. Moreover, it was found that heterogeneity in herbivore communities maintains intraspecific variation in defence genes [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the heterogeneous distribution of herbivores can shape plant defensive chemistry above ground [7][8][9]. Moreover, it was found that heterogeneity in herbivore communities maintains intraspecific variation in defence genes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Insect herbivores, the most abundant and diverse plant consumers, have long been suspected to play an important role in this context [6]. Recent studies demonstrate that herbivore abundance can covary with the expression of plant defence metabolites [7], that the exclusion of phytophagous insects can lead to a relaxation of defences within a few generations [8] and that defence genes are under differential selection across environments [9,10]. Together, these studies show that the temporal and spatial variation in above-ground herbivore communities can shape plant defensive chemistry.…”
mentioning
confidence: 99%
“…In the first example, Agrawal et al [75] used insecticides to manipulate densities of arthropods feeding on genetically diverse experimental field populations of evening primrose (Oenothera biennis). They then followed the evolutionary dynamics of these populations for four generations.…”
Section: Species Interactions and Evolutionmentioning
confidence: 99%
“…This important diversification suggests that particular metabolic systems have been recruited through natural selection when the set of compounds that they produce address specific ecological needs. Interactions with insects are important selection pressures that have sculpted plant metabolism, and many plant metabolites protect against herbivore attack and physical damage (3)(4)(5). The timely production of particular secondary metabolites in response to insect attack benefits plants by decreasing the costs of constitutive metabolite production.…”
mentioning
confidence: 99%